KANKER OVARIUM DISGERMINOMA - Hegaria Rahmawati; Darmawaty ER; Ruland DN Pakasi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Ovarian cancer is a female reproductive organ malignancy and the second most common gynaecological type cancers. World Health Organisation classifies ovarian cancer based on their origin: superficial stroma-epithelium tumour, cord-stroma sex tumour, and germ cell tumour originated from germinal cells (yolk sac). Epithelium type of ovarian cancer is common, while the germinal type is rare and can be found in teenagers and young women aged 16-20 years old. A case of suspected dysgerminomas ovarian cancer grade IIIA was reported in a 12 years old girl. The diagnosis was established by tumour markers, USG/CT Scan of abdomen, surgery, and frozen section evaluations. The reviewer expected better survival prognosis after surgery and three cycles of chemotherapy combinations were executed. The evaluations of when serial tumour markers CA-125 were suggested during chemotherapy to detect any recurrences factors possibility of the related cancer.